Strategi public relation dalam meningkatkan brand awareness perbankan syariah di indonesia - afanin, alfenda nafiah (Maliki Interdisciplinary Journal, 2024)
In fierce competition with conventional banking, Islamic banking in Indonesia has shown significant growth. Indonesia shows significant growth. In order for the public to continue to remember and choose Islamic banking, public relations of Islamic banks need to have a clear and targeted communication strategy. have a clear and targeted communication strategy. With the right strategy, Islamic banks can ensure that their communication messages are effective in increasing public awareness. in increasing public awareness. This research aims to systematically analyze the various public relations strategies implemented by Islamic banks in Indonesia. Through literature review and case analysis, this research identifies best practices, as well as social responsibility programs to increase brand awareness and responsibility programs to increase brand awareness and public trust towards Islamic banking